Crystal Structure and Immunogenicity of the DS-Cav1-Stabilized Fusion Glycoprotein From Respiratory Syncytial Virus Subtype B - M. Gordon Joyce; Amy Bao; Man Chen; Ivelin S. Georgiev; Li Ou; Tatsiana Bylund; Aliaksandr Druz; Wing-Pui Kong; Dongjun Peng; Emily J. Rundlet; Joseph G. Van Galen; Shuishu Wang; et al. (Case Western Reserve University, 2019)
Background: Respiratory syncytial virus (RSV) subtypes, A and B, co-circulate in annual epidemics and alternate in dominance. We have shown that a subtype A RSV fusion (F) glycoprotein, stabilized in its prefusion conformation by DS-Cav1 mutations, is a promising RSV-vaccine immunogen, capable of boosting RSV-neutralizing titers in healthy adults. In both humans and vaccine-tested animals, neutralizing titers elicited by this subtype A DS-Cav1 immunogen were ~ 2- to 3-fold higher against the homologous subtype A virus than against the heterologous subtype B virus. Methods: To understand the molecular basis for this subtype difference, we introduced DS-Cav1 mutations into RSV strain B18537 F, determined the trimeric crystal structure, and carried out immunogenicity studies. Results: The B18537 DS-Cav1 F structure at 2-Å resolution afforded a precise delineation of prefusion F characteristics, including those of antigenic site Ø, a key trimer-apex site. Structural comparison with the subtype A prefusion F indicated 11% of surface residues to be different, with an alpha-carbon root-mean-square deviation (RMSD) of 1.2 Å; antigenic site Ø, however, resulted in 23% of its surface residues and had an alpha-carbon RMSD of 2.2 Å. Immunization of vaccine-tested animals with DS-Cav1-stabilized B18537 F induced neutralizing responses ~100-fold higher than with postfusion B18537 F. Notably, elicited responses neutralized RSV subtypes A and B at similar levels and were directed towards both conserved equatorial and diverse apical regions. Conclusion: We propose that structural differences in apical and equatorial sites-coupled to differently focused immune responses-provide a molecular explanation for observed differences in elicited subtype A and B neutralizing responses. Keywords: antigenic site; crystal structure; epitope; fusion glycoprotein; immunogenicity; neutralization; RSV subtype; vaccine